Improving the completeness and transparency of reports of randomized trials in oral health: the CONSORT statement. - Needleman, I; Worthington, H; Moher, D; Schulz, K; Altman, D (2008)
PURPOSE: Randomized trials provide essential evidence of the effect of interventions in oral health. Such trials need to be appraised by readers in order to decide whether to incorporate new findings into clinical practice and policy in a timely manner. The CONSORT (Consolidated Standards of Reporting of Trials) Statement is a guidance to facilitate reporting of randomized controlled trials (RCTs) and was first introduced in 1996. The purpose of this article is to highlight the importance of rigorous reporting of trials in oral health and to discuss the impact of CONSORT on trial reporting. RESULTS: Empirical studies demonstrate that key aspects of trial methods influence the size of estimates of studied interventions and bias is a plausible mechanism for some of this effect. Complete and transparent reporting of these methods allows appraisal of the value of trials to be undertaken and the potential for bias to be estimated. Systematic reviews have shown that the reported quality of trials in dentistry is poor, thus hindering the understanding of the value of individual trials. Since 1996, CONSORT has been adopted by hundreds of medical journals, international editorial groups, and five dental journals. A systematic review has shown that the quality of reporting of trials improves in journals that have adopted this guidance, although with significant variation, most likely due to differing levels of editorial adherence to it.